The Music Master; Novelized from the Play - Klein, Charles, 1867-1915 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Music Master" by Charles Klein is a novelized adaptation of a play that explores themes of love, betrayal, and the struggles of an artist. Written in the early 20th century, the story centers around Anton Von Barwig, a dedicated conductor who faces personal and professional turmoil following the departure of his wife and the challenges of his artistic career in a new country. The beginning of the novel introduces Anton struggling with unhappiness and turmoil in his life as the conductor of the Leipsic Philharmonic Orchestra. It depicts a rehearsal that spirals out of control due to Anton$1 (Bs distraction from troubling thoughts about his wife, Elene, and the influence of another man in her life. As he grapples with self-doubt and anger over this betrayal, we see the depth of his emotions through his interactions with the orchestra and his close friend Poons, revealing not only his artistic dedication but also his fragile state of mind regarding family and love. The opening sets the tone for a compelling exploration of loss and the quest for redemption through music and personal connections. (This is an automatically generated summary.)s
Release date is 2007-11-24
E-text prepared by Al Haines
Keywords: Fathers and daughters -- Fiction; Social classes -- Fiction; Musicians -- Fiction; Determination (Personality trait) -- Fiction; Attitude change -- Fiction